Meningkatkan Keterampilan Guru Matematika Dalam Menggunakan Model Pembelajaran Melalui Mgmp Di Kabupaten Bengkulu Utara - suwarni, Suwarni (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2017)
The purpose of the writer is to know the teacher skills in using Mathematical learning models made by master, obtained information that the attainment of competencies by students as it poured in KKM in schools in the region of North Bengkulu Mathematics subjects especially on average under the KKM. Beside that, the result of organized supervision in October 2015 gives the conclusion that the teachers of mathematics in the schools is not executing flawlessly a learning model that had them pour in the lesson plan preparation. Problems that have been found in the field will be solved based on the study of theories that have been put forward earlier performing the activities of district level workshop for teachers of Mathematics there in North Bengkulu Regency by 2015. The real workshop with activities following the procedure as above will give you the skills to participants of the workshop in terms of measures the use of a proper learning model, thus giving the feel of learning that enable students who in turn give the results of the achievement of the KKM is satisfactory.